Penyuluhan Pembuatan Olahan Daging Bekamal dalam Meningkatkan Nilai Jual Produk di Desa Alasbuluh Kecamatan Wongsorejo Kabupaten Banyuwangi - Yahya Nuruddin; Mahani Faiza Aulia; Desy Afriana Litasari; Andy Setiawan; Farnida Dwi Kiranti; Ayu Novitri Ramadani; Galuh Windy Apriliani; Vicky Adi Setyawan; Sefri Ton; Dani Agung Wicaksono; Ninik Sri Rahayu Wilujeng; Nadia Maharani (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Bekamal is a local Banyuwang processed food product. Bekamal is actually a preservation method that uses salt and sugar. Generally, people make Bekamal from beef or goat meat. The meat is finely chopped, then salt and sugar are added and placed in a closed container for 1 to 3 months. Bekamal has advantages, including low cholesterol levels, and can be processed into various kinds of food preparations, such as bekamal chilli sauce. Many people don't know how to make bekamal or how to process it. The extension programme is able to provide knowledge and experience on how to make bekamal, a local Banyuwangi product.